2016
DOI: 10.1037/lhb0000178
|View full text |Cite
|
Sign up to set email alerts
|

The habitual female offender inside: How psychopathic traits predict chronic prison violence.

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 139 publications
(248 reference statements)
1
28
0
3
Order By: Relevance
“…Affective psychopathic traits have been found to differentiate women responsible for the most severe forms of violence [27], and the present study extends on this by finding affective psychopathic traits were positively associated with proactive aggression. Thus, women who lack remorse and empathy, and have a callous disregard for others engage in higher levels of goal-directed aggression.…”
Section: Accepted Manuscriptsupporting
confidence: 74%
See 2 more Smart Citations
“…Affective psychopathic traits have been found to differentiate women responsible for the most severe forms of violence [27], and the present study extends on this by finding affective psychopathic traits were positively associated with proactive aggression. Thus, women who lack remorse and empathy, and have a callous disregard for others engage in higher levels of goal-directed aggression.…”
Section: Accepted Manuscriptsupporting
confidence: 74%
“…However, this is yet to be explored in emerging adult women and as a moderator between psychopathy and violence. This is problematic as there are well-established sex differences in psychopathy, emotion, and aggressive and violent behavior, as well as the link between RSA and aggression [27,29,51,[65][66][67][68][69]. Thus, the present study will be the first female dedicated research to explore the moderating role of neurobiological function (RSA) in the link between psychopathic traits and reactive and proactive aggression and violent behavior.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…В недавних работах, посвященных совершению в тюрьмах таких преступлений, как убийство, нападение с отягчающими обстоятельствами, захват заложников и учинение массовых беспорядков, было показано, что эти насильственные действия очень редко совершаются заключенными-женщинами [50]. Кроме того, изучалась связь между прошлой криминальной историей женщин-заключенных и их поведением в тюрьмах [60]. По мнению некоторых ученых, межличностные взаимоотношения женщин-заключенных могут становиться более неустойчивыми, чем считалось ранее [61].…”
Section: фактор полаunclassified
“…Although limited, research has explored potential predictors of institutional misconduct by utilizing female-only offender samples. For instance, prior studies of female-only samples found age at first commitment, having a mental health disorder, offense type, gang affiliation, past violent criminal history, impulsivity, and callous and antisocial psychopathic traits predicted violent and nonviolent institutional misconducts (Blackburn & Trulson, 2010;Thomson, Towl & Centifanti, 2016). These predictors have been found to predict institutional misconducts in males as well (e.g., Arbach-Lucioni et al, 2012;Edens, Poythress, Lilienfeld, Patrick & Test, 2008;Ruddell & Gottschall, 2011).…”
Section: Predictors Of Institutional Misconduct For Women Offendersmentioning
confidence: 97%